The Balance Between Professional Ethics and Legal Perspectives in Medicine - Tri Agus Haryono; Hj. Yeti Kurniati; Hj. Hernawati RAS (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research examines the complex interactions between professional ethics, legal perspectives, and developments in medical technology in medical practice. Conflicts often occur when the ethical principles underlying medical practice conflict with existing legal constraints, especially as technological advances accelerate. Through in-depth analysis of complex clinical situations and recent legal regulatory developments, this research aims to understand how physicians navigate the moral challenges that arise from the use of advanced technologies in healthcare while considering the existing legal framework. The results illustrate the need for a careful balance between technological innovation, ethical principles, and compliance with legal regulations to ensure responsible and quality medical practice